Determinants of CEO pay: an examination of the Hadrami charitable foundations - Afif, Ameen Ali Ahmed (2016)
Although the nonprofit sector is enormous, corporate governance, particularly the role of CEO pay, has received very little attention in this sector. This study is examining CEO pay in Hadrami nonprofit organizations. For this purpose, this study uses firm characteristics (sector of the organization and organizational size) and CEO characteristics (CEO's qualifications, CEO's experience, CEO duality, and CEO's tenure) to ex-mine the impact on CEO pay. A web-based questionnaire was considered an appropriate method for this study. The sample was selected from nonprofit organizations listed on Ministry of Labor and Social Affairs that operate in Hadramout (90 charitable foundations). A total of 57 CEOs responded to the questionnaire, generating a 63.33% response rate. Using multiple regression analysis, the results of this study indicate that the size of organization and CEO's qualifications have significant influence on CEO pay. Other variables namely, sector of the organization, CEO's experience, CEO duality, and CEO's tenure have no significant impact on CEO pay.